Characterizing left ventricular stiffness in women with signs and symptoms of ischemia with no obstructive coronary arteries. (3rd October 2022) - Wei, J; Samuels, B; Oneglia, A; Tjoe, B; Gomez, J M D; Manchanda, A S; Samuel, T J; Azarbal, B; Kwan, A C; Anderson, R D; Petersen, J W; Berman, D S; et al.
Abstract: Background: Women with signs and symptoms of ischemia and no obstructive coronary arteries (INOCA) have evidence of diastolic dysfunction and are at increased risk of developing heart failure with preserved ejection fraction (HFpEF). However, mechanisms contributing to HFpEF development are poorly understood and often attributed to underlying cardiovascular risk factors. Purpose: To compare clinical, invasive, and imaging parameters in women with suspected INOCA and various degrees of left ventricular (LV) stiffness (as measured by invasive end-diastolic pressure [EDP]/end diastolic volume [EDV]). Methods: Women with suspected INOCA underwent invasive LV pressure-volume loop analysis at rest and coronary function testing with a Doppler wire in the left anterior descending artery. Intracoronary vasoactive substances (adenosine, acetylcholine, nitroglycerin) were infused into the left main artery, as published. Rest and adenosine stress cardiac magnetic resonance (CMR) imaging was performed to evaluate LV function, structure, perfusion, and fibrosis. Women in different tertiles of EDP/EDV ratio were compared using t-tests. Results: A total of 62 women with complete invasive data were included; 2 did not complete CMR. Compared to the lower EDP/EDV tertile, women in the upper tertile were older, had higher ejection fraction, higher mass/volume ratio, worse diastolic function, greater aortic stiffness and worse coronary microvascular function (Table 1). Traditional cardiovascular risk factors were not significantly different. Conclusion: Among women with INOCA, older age, coronary microvascular dysfunction, and aortic stiffness were related to greater LV stiffness at rest. Those with the highest EDP/EDV ratio had hyperdynamic LV systolic function and the smallest LV size. More work is needed to understand contribution of coronary microvascular dysfunction to HFpEF progression. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): National Institutes of HealthErika Glazer Women's Heart Health Project